Repair strategies by children with history of cleft lip and/or palate in other-initiated repair sequence - Saad, Mohammad Azannee; Mohd Jan, Jariah (UM Press, 2020)
This paper identifies repair strategies by children with history of cleft lip and/or palate (CL/P) following the initiation by their conversational partners. Specifically, it analyses the strategies that are used by these children to construct the repair turn. Data come from approximately 7-hour recordings of everyday interaction during family activities such as meal time. Data collection is guided by the principle of Conversation Analysis (CA). CA also informs the study on turn-byturn examination while the coding of repair strategy adopts Philip’s Repair Response (2008). Findings highlight the limited ability of these children to give immediate success to repair where majority of their repair strategy is inappropriate. Other strategies include close-ended repair and repetition of trouble source that further show their poor pragmatic functions. This study gives evidence on the interactional challenge of children with history of CL/P that can benefit speech and language treatment plan.